2014
DOI: 10.1371/journal.pone.0085487
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Analysis of Plasmids in Human and Animal Associated Arcobacter Species

Abstract: In this study, we report the screening of four Arcobacter species for the presence of small and large plasmids. Plasmids were present in 9.9% of the 273 examined strains. One Arcobacter cryaerophilus and four Arcobacter butzleri plasmids were selected for further sequencing. The size of three small plasmids isolated from A. butzleri and the one from A. cryaerophilus strains ranged between 4.8 and 5.1 kb, and the size of the large plasmid, isolated from A. butzleri, was 27.4 kbp. The G+C content of all plasmids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
2
15
0
1
Order By: Relevance
“…Our results suggest Arcobacter members as potential keystone players involved in conjugative plasmid acquisition and plasmid shuttling through WWTPs, before potential redistribution to broader phylogenetic recipients from both Gram‐types, including freshwater copiotrophs. This is supported by the literature, as Arcobacter ‐related members were reported to be associated with conjugative plasmid transfer (Douidah et al., ), antibiotic resistance (Zacharow et al., ) and survival to changing environmental conditions (Van Driessche & Houf, ).…”
Section: Discussionsupporting
confidence: 65%
“…Our results suggest Arcobacter members as potential keystone players involved in conjugative plasmid acquisition and plasmid shuttling through WWTPs, before potential redistribution to broader phylogenetic recipients from both Gram‐types, including freshwater copiotrophs. This is supported by the literature, as Arcobacter ‐related members were reported to be associated with conjugative plasmid transfer (Douidah et al., ), antibiotic resistance (Zacharow et al., ) and survival to changing environmental conditions (Van Driessche & Houf, ).…”
Section: Discussionsupporting
confidence: 65%
“…Jacquiod et al 53 described Arcobacter from wastewater treatment plants as a keystone player involved in shuttling antibiotic resistance genes between distant gram-positive and gram-negative phyla. It has also been reported that the Arcobacter spp are associated with conjugative plasmid transfer 54 and survival in changing environmental conditions 55 . The second most abundant bacterial species detected in the Pinheiros River is the well-characterized exoelectrogenic Geobacter_uc from the δ-Proteobacteria class 56 .…”
Section: Discussionmentioning
confidence: 98%
“…Described resistance determinants are mostly located chromosomal, and no antimicrobial resistance genes have been identified on plasmids, yet. Until now, only a few studies have reported the presence of plasmids in the genus Aliarcobacter ( Harrass et al, 1998 ; Douidah et al, 2014 ; On et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%